RISK MITIGATION IN SUPPLY CHAIN DISRUPTION DURING PANDEMIC COVID-19 IN EPC PROJECT, STUDY CASE PT XYZ - Arpan Marwazi Lubis; Maria Widyarini; Oki Sunardi (Jurnal Ekonomi, 2023)
The COVID-19 pandemic, which began in early 2019 and persists to this day in 2022, stands as one of the most significant global disasters in recent years. Beyond the staggering number of fatalities and hospitalizations, its impact encompasses widespread economic repercussions, extensive business interruptions, and significant hardships worldwide. Its spread has profoundly affected various sectors of the global economy, including manufacturing, hospitality and tourism, finance, food and beverage, as well as the construction industry in Indonesia. Numerous projects in Indonesia suffered delays and increased costs due to the pandemic. Construction activities abruptly ceased at various sites, leading to a stagnation in productivity. In light of these circumstances, this study focuses on the initial challenges encountered in managing the COVID-19 crisis and its specific implications on the construction sector. This study investigated the impact of the COVID-19 pandemic on EPC (Engineering, Procurement, and Construction) companies in Indonesia. The analysis was conducted based on feedback obtained from 11 respondents belonging to SCM (Supply Chain Management) Departments, comprising SCM managers and Logistics managers from major international EPC companies operating in oil, gas, power, petrochemicals, and related services engaged in ongoing EPC projects within Indonesia. These respondents shared insights derived from their experiences in addressing the disruptive effects of the pandemic. They highlighted the overall negative impacts encountered, newly emerged opportunities, and ongoing efforts in risk management. The reported adverse effects encompassed significant project delays, challenges in acquiring materials on time, reduced productivity rates, increased logistics expenses, escalations in material costs, shifts in transportation methods (from sea freight to air freight) to meet construction schedules, among other challenges. The Supply Chain disruption caused various impacts, particularly on material, finance, and information flows. Material movements and deliveries experienced significant delays due to disruptions. Finance flows, including payment terms for both sellers and buyers, were also affected, causing disruptions in transactions. Information flow across multiple aspects, including human resources, material stock information, quotations, inspections, Health, Safety, and Environment (HSE), and scheduling, faced challenges. Risk management strategies were significantly bolstered to address these issues, focusing on enhancing safety measures (HSE) and mitigating other project risks like delivery delays and handover issues. Safety measures were intensified, mandating employees to wear medical face masks, undergo body temperature checks below 37 degrees Celsius, adhere to social distancing protocols, implement staggered construction operations, provide COVID-19-related training, conduct temperature checks before entry to workplaces, frequently administer antigen tests/PCR tests, and other precautionary measures to ensure safety and minimize the risk of virus transmission.